2004
DOI: 10.1073/pnas.0404372101
|View full text |Cite
|
Sign up to set email alerts
|

Subfertility and defective folliculogenesis in female mice lacking androgen receptor

Abstract: The roles of the androgen receptor (AR) in female fertility and ovarian function remain largely unknown. Here we report on the generation of female mice lacking AR (AR ؊/؊ ) and the resulting influences on the reproductive system. Female AR ؊/؊ mice appear normal but show longer estrous cycles and reduced fertility. The ovaries from sexually mature AR ؊/؊ females exhibited a marked reduction in the number of corpora lutea. After superovulation treatment, the AR ؊/؊ ovaries produced fewer oocytes and also showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
217
5
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(241 citation statements)
references
References 41 publications
16
217
5
2
Order By: Relevance
“…Although follicles and corpora lutea at all developmental stages were still present, corpora lutea numbers were clearly reduced in 8-week-old AR Ϫ/Ϫ mutants ( Fig. 2 b and f ), similar to that observed in another mouse line (20). Expected apoptosis was seen in atretic follicles by activated caspase-3 immunohistochemistry assays (Fig.…”
Section: Resultssupporting
confidence: 49%
“…Although follicles and corpora lutea at all developmental stages were still present, corpora lutea numbers were clearly reduced in 8-week-old AR Ϫ/Ϫ mutants ( Fig. 2 b and f ), similar to that observed in another mouse line (20). Expected apoptosis was seen in atretic follicles by activated caspase-3 immunohistochemistry assays (Fig.…”
Section: Resultssupporting
confidence: 49%
“…Considering the results of the present study in this context, we can infer that T has a dual function of modulating folliculogenesis and regulating embryo implantation in female reproduction. This hypothesis is supported by the observations of reduced fertility in homozygous female AR knockout mice, which is not only associated with fewer oocytes after super-ovulation and follicular atresia but also with impaired uterine hypertrophy and endometrial growth, which are required for implantation [19,20]. However, in the present study, basal T levels showed no correlation with ovarian stimulus metrics, such as the E 2 levels on the HCG day, number of oocytes retrieved, and the total dose of gonadotropins.…”
Section: Discussionmentioning
confidence: 69%
“…The promoter region of p21 contains an ARE and, therefore, the AR likely regulates its expression. The marked reduction in p21 expression in the Ar-null ovary during the peri-ovulatory stage may disturb the process of terminating proliferation and explain the increased cell apoptosis and follicular atresia in these Ar 2 K/K mice (Hu et al 2004, Walters et al 2010.…”
Section: Ar-induced Genes In Follicular Developmentmentioning
confidence: 99%
“…Cyclin-dependent kinase inhibitor-1/p21 p21 is known to play a role in GC luteinization (Robker & Richards 1998), and is downregulated in Ar 2 K/K mice ovaries (Hu et al 2004). The promoter region of p21 contains an ARE and, therefore, the AR likely regulates its expression.…”
Section: Ar-induced Genes In Follicular Developmentmentioning
confidence: 99%